Hot spots of retroviral integration in human CD34+ hematopoietic cells - Cattoglio, Claudia; Facchini, Giulia; Sartori, Daniela; Antonelli, Antonella; Miccio, Annarita; Cassani, Barbara; Schmidt, Manfred; von Kalle, Christof; Howe, Steve; Thrasher, Adrian J.; Aiuti, Alessandro; Ferrari, Giuliana; et al. (Blood, 2007)
Insertional oncogenesis is a possible consequence of the integration of gamma-retroviral (RV) or lentiviral (LV) vectors into the human genome. RV common insertion sites (CISs) have been identified in hematopoietic malignancies and in the nonmalignant progeny of transduced hematopoietic stem/progenitor cells (HSCs), possibly as a consequence of clonal selection in vivo. We have mapped a large number of RV and LV integrations in human CD34+ HSCs, transduced in vitro and analyzed without selection. Recurrent insertion sites (hot spots) account for more than 21% of the RV integration events, while they are significantly less frequent in the case of LV vectors. RV but not LV hot spots are highly enriched in proto-oncogenes, cancer-associated CISs, and growth-controlling genes, indicating that at least part of the biases observed in the HSC progeny in vivo are characteristics of RV integration, already present in nontransplanted cells. Genes involved in hematopoietic and immune system development are targeted at high frequency and enriched in hot spots, suggesting that the CD34+ gene expression program is instrumental in directing RV integration. The lower propensity of LV vectors for integrating in potentially dangerous regions of the human genome may be a factor determining a better safety profile for gene therapy applications.